1976
DOI: 10.1126/science.790568
|View full text |Cite
|
Sign up to set email alerts
|

Structural Domains of Transfer RNA Molecules

Abstract: In this article, we have described various detailed features of the conformation of yeast tRNA(Phe) revealed by recent refinement analysis of x-ray diffraction data at 2.5 A resolution. The gross features of the molecule observed in the unrefined version have been largely confirmed and a number of new features found. The unique role of the ribose 2' hydroxyl groups in maintaining a series of nonhelical conformations in this RNA molecule has become apparent. Many of these features are a direct consequence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
397
1
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 527 publications
(416 citation statements)
references
References 31 publications
16
397
1
2
Order By: Relevance
“…Various aptamers were constructed containing the theophylline-binding core motif to determine which systems were suitable for NMR studies, and their ligand-binding affinities were measured at 25 8C+ The hairpin-loop region of the original ⌬TCT-4 theophylline-binding RNA (Jenison et al+, 1994) was observed to cleave over time in Mg 2ϩ -containing buffer (not shown); therefore other constructs (Fig+ 1B) containing the conserved core nucleotides and a stable GAAA-tetraloop motif were synthesized+ The sequence of the terminal stem was also changed in these constructs relative to the wild-type ⌬TCT-4 sequence to improve transcription and for compatibility with the sequence requirements for hammerhead ribozyme cleavage that was used to posttranscriptionally process the theophylline-binding RNAs to give a homogeneous 39 end (see Materials and methods)+ The ⌬-33 RNA contains a GAAA tetraloop with a flanking 3-bp stem connected to the conserved core, and this RNA has the same binding affinity for theophylline as the original wild-type ⌬TCT-4 sequence+ The ⌬-31 construct (Fig+ 1B) eliminates a single G•C pair adjacent to the theophylline-binding core, thus reducing the size of the RNA+ Comparative sequence analysis of the original in vitro selection experiment indicated that only 2 bp were required to close the upper stem (Jenison et al+, 1994)+ However, the ⌬-31 construct binds theophylline with a factor of ;15 lower affinity than the wild-type ⌬TCT-4 RNA (Fig+ 1B)+ This suggests that the GAAA tetraloop and the theophylline-binding core may need to be separated by a minimum number of helical residues so that the tetraloop does not affect the structure and/or dynamics of the core+ The ⌬-40 construct binds theophylline with approximately eight times lower affinity than the original ⌬TCT-4 aptamer or the ⌬-33 construct (Fig+ 1B)+ This result was very surprising because this RNA has the same sequence as ⌬-33, except for a flip of 2 bp in the hairpin stem flanking the conserved core region+ In the structure of the ⌬-33 RNA-theophylline complex, the G11 stacks on top of A10 within the core region of the complex (Zimmermann et al+, 1997)+ Thus flipping the G11-C20 pair replaces a stable purine-purine stack with a less stable pyrimidine-purine stack and may be the reason for the lower binding affinity for the ⌬-40 construct+ All possible base pair sequences were observed at this position in the original selection experiment (Jenison et al+, 1994), indicating that the isolates from in vitro selections contain a range of binding activities, and quantitative experiments are required to define more precisely the functionally important positions+ Functional group interference mapping is consistent with a U-turn U-turns are a common structural motif in RNA and are stabilized by intraturn base-backbone H-bonding interactions (Quigley & Rich, 1976;Jucker & Pardi, 1995)+ U24 is part of a U-turn in the core of this RNA aptamer (Zimmermann et al+, 1997) where the U24 29-hydroxyl is hydrogen bonded to the N7 of G26 (Fig+ 5A)+ As seen in Table 1, replacement of the U24 29-hydroxyl with 29-deoxy strongly inhibits the ability of the RNA to bind theophylline (.90-fold lower affinity), presumably by disrupting this U24 29OH-to-G26 N7 H-bond+ However, disruption of this H-bond by the 7-deaza, 29-deoxy G26 base modification has a much smaller effect on theophylline binding+ The effect of the 7-deaza substitution is most appropriately addressed by comparing relative binding affinities of 7-deaza, 29-deoxy G26 to 29-deoxy G26 (Table 1), where...…”
Section: Nucleotides Flanking the Core Can Affect Theophylline Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various aptamers were constructed containing the theophylline-binding core motif to determine which systems were suitable for NMR studies, and their ligand-binding affinities were measured at 25 8C+ The hairpin-loop region of the original ⌬TCT-4 theophylline-binding RNA (Jenison et al+, 1994) was observed to cleave over time in Mg 2ϩ -containing buffer (not shown); therefore other constructs (Fig+ 1B) containing the conserved core nucleotides and a stable GAAA-tetraloop motif were synthesized+ The sequence of the terminal stem was also changed in these constructs relative to the wild-type ⌬TCT-4 sequence to improve transcription and for compatibility with the sequence requirements for hammerhead ribozyme cleavage that was used to posttranscriptionally process the theophylline-binding RNAs to give a homogeneous 39 end (see Materials and methods)+ The ⌬-33 RNA contains a GAAA tetraloop with a flanking 3-bp stem connected to the conserved core, and this RNA has the same binding affinity for theophylline as the original wild-type ⌬TCT-4 sequence+ The ⌬-31 construct (Fig+ 1B) eliminates a single G•C pair adjacent to the theophylline-binding core, thus reducing the size of the RNA+ Comparative sequence analysis of the original in vitro selection experiment indicated that only 2 bp were required to close the upper stem (Jenison et al+, 1994)+ However, the ⌬-31 construct binds theophylline with a factor of ;15 lower affinity than the wild-type ⌬TCT-4 RNA (Fig+ 1B)+ This suggests that the GAAA tetraloop and the theophylline-binding core may need to be separated by a minimum number of helical residues so that the tetraloop does not affect the structure and/or dynamics of the core+ The ⌬-40 construct binds theophylline with approximately eight times lower affinity than the original ⌬TCT-4 aptamer or the ⌬-33 construct (Fig+ 1B)+ This result was very surprising because this RNA has the same sequence as ⌬-33, except for a flip of 2 bp in the hairpin stem flanking the conserved core region+ In the structure of the ⌬-33 RNA-theophylline complex, the G11 stacks on top of A10 within the core region of the complex (Zimmermann et al+, 1997)+ Thus flipping the G11-C20 pair replaces a stable purine-purine stack with a less stable pyrimidine-purine stack and may be the reason for the lower binding affinity for the ⌬-40 construct+ All possible base pair sequences were observed at this position in the original selection experiment (Jenison et al+, 1994), indicating that the isolates from in vitro selections contain a range of binding activities, and quantitative experiments are required to define more precisely the functionally important positions+ Functional group interference mapping is consistent with a U-turn U-turns are a common structural motif in RNA and are stabilized by intraturn base-backbone H-bonding interactions (Quigley & Rich, 1976;Jucker & Pardi, 1995)+ U24 is part of a U-turn in the core of this RNA aptamer (Zimmermann et al+, 1997) where the U24 29-hydroxyl is hydrogen bonded to the N7 of G26 (Fig+ 5A)+ As seen in Table 1, replacement of the U24 29-hydroxyl with 29-deoxy strongly inhibits the ability of the RNA to bind theophylline (.90-fold lower affinity), presumably by disrupting this U24 29OH-to-G26 N7 H-bond+ However, disruption of this H-bond by the 7-deaza, 29-deoxy G26 base modification has a much smaller effect on theophylline binding+ The effect of the 7-deaza substitution is most appropriately addressed by comparing relative binding affinities of 7-deaza, 29-deoxy G26 to 29-deoxy G26 (Table 1), where...…”
Section: Nucleotides Flanking the Core Can Affect Theophylline Bindingmentioning
confidence: 99%
“…The metal-binding site in the core of this RNA aptamer could perform a number of functions critical to theophylline binding and caffeine discrimination+ By stabilizing the high density of negative charge created by the juxtaposition of multiple phosphate groups (C22, U23, U24, G25) in this turn (Fig+ 6), the metal could facilitate folding of the core+ This is a critical region in the core of the RNA because it allows interactions between conserved residues of the two internal loops (Fig+ 1B) that are required for the formation of the ligandbinding pocket+ Residues U24, G25, and G26 are part of the U-turn (Quigley & Rich, 1976;Jucker & Pardi, 1995;Zimmermann et al+, 1997) that helps bring the upper and lower loops of the RNA together to form the ligand-binding site+ Another potential role for the metal (Zimmermann et al+, 1997), and the arrow points to the N7 of residue A28 that, when modified to 7-deaza, showed much lower affinity for theophylline (see text)+ is to correctly orient the bases of residues C22 and U24 that hydrogen bond to theophylline, forming the critical base-triple that mediates the molecular discrimination of this RNA aptamer (Zimmermann et al+, 1997)+ Although the data in Figures 3 and 6 clearly define the region of the metal-binding site, additional data such as thiophosphate interference-type experiments are needed to try to identify uniquely specific ligands on the RNA that are coordinating the metal+…”
Section: Nucleotides Flanking the Core Can Affect Theophylline Bindingmentioning
confidence: 99%
“…From the preceding, an extended anticodon hairpin signature can be proposed+ This signature summarizes all the available phylogenetic and structural considerations and includes interaction as characterized above between ribose33 and base35 (Fig+ 5)+ 1+ The 31-39 pair, which is the last base pair of the anticodon stem, is of the Watson-Crick type in more than 90% of the instances+ Besides the GϭC and CϭG pairs (48%), the A31-U39 pairs dominate (37%) and are systematically modified into A31-⌿39 pairs (Auffinger & Westhof, 1998a;Yarian et al+, 1999)+ The systematic modification of A31-U39 pairs into A31-⌿39 pairs has been shown to strengthen the anticodon hairpin structure to a level probably equivalent to hairpins with C31ϭG39 or G31ϭC39 pairs by forming a water mediated base-backbone interaction (Auffinger & Westhof, 1998a)+ 2+ Among all the tRNA sequences, 93% of the 32•38 oppositions can be assigned to two families of isosteric base pairs )+ The first family (86%) is characterized by the formation of a bifurcated hydrogen bond between the carbonyl group of a pyrimidine at position 32 and an amino group of a base located at position 38, and comprises the C32•A38, U32•A38, U32•C38, and C32• C38 pairs+ The second family (7%) implies the formation of a U32•U38 non-Watson-Crick pair+ A third family (7%) comprises a set of 11 infrequent 32•38 sequences that are not isosteric to the base pairs found in families 1 or 2+ The proportion of GϭC or CϭG pairs is close to zero+ 3+ A (U33)N3-H + + + OR-P(36) hydrogen bond is recurrently observed in tRNA crystal structures and is part of the signature of U-turns and, thus, more specifically of the anticodon hairpin signature (Quigley & Rich, 1976;Jucker & Pardi, 1995)+ 4+ A conserved interaction that utilizes either the donor or the acceptor hydrogen bond potential of the (U33)O29-H group links the ribose of U33 to the base at position 35+ With a purine at position 35, a (U33)O29-H + + + N7(R35) bond is formed (Quigley & Rich, 1976), with a pyrimidine at position 35, a (U33)O29 + + + H-C5(Y35) interaction is observed+ 5+ Last, a stacking interaction involving the aromatic cycle of U33 and the OR atom of the phosphate group of nucleotide 35 is recurrently observed in all the known tRNA structures (Quigley & Rich, 1976)+…”
Section: Extended Canonical Anticodon Loop Structurementioning
confidence: 99%
“…As inferred from several biochemical studies, a canonical three-dimensional structure of the anticodon hairpin is supposed to be essential for the binding of tRNA molecules to the ribosomal binding sites (Schnitzler & von Ahsen, 1997;von Ahsen et al+, 1997;Ashraf et al+, 1999aAshraf et al+, , 1999bCate et al+, 1999)+ Up to now, the anticodon structure is defined by the presence of an array of conserved and semiconserved nucleotides+ Among them, a uridine is recurrently observed at position 33; the base at position 32 is generally a pyrimidine (Y); the bases at positions 37 and 38 are essentially purines (R); the three bases at the anticodon positions 34, 35, and 36 display a nearly equal proportion of the four nucleotides; positions 34 and 37 accept a large number of modified nucleotides; a very limited number of modified nucleotides are observed at positions 35 and 36 (Grosjean et al+, 1982;Auffinger & Westhof, 1998b); uridines when present at position 39 are mainly modified into pseudouridines (Auffinger & Westhof, 1998a;Yarian et al+, 1999)+ These sequence conservations are mandatory, in the vast majority of the cases, for the formation of functional canonical anticodon hairpin structures that include the first motif that has been characterized in RNA molecules, namely the U-turn motif (Quigley & Rich, 1976)+ The tertiary structure of the anticodon loop U-turn is usually defined by the formation of a (U33)N3-H + + + OR-P(36) hydrogen bond, a stacking interaction between the aromatic cycle of U33 and the OR atom of residue 35, and a sharp reversal of the phosphodiester backbone following U33 (Quigley & Rich, 1976)+ Additionally, on top of the U-turn motif involving residues 33-36, it has been shown, on the basis of crystallographic and phylogenetic data, that the conservation of a set of non-Watson-Crick isosteric base pairs at position 32•38 is essential for the formation of a canonical hairpin structure )+ All these tertiary interactions are part of the signature of the tRNA anticodon loop+ In addition, from the yeast tRNA Phe structure, it has been inferred that a (U33)O29-H + + + N7(A35) hydrogen bond is formed (Quigley & Rich, 1976)+ Indeed, such a hydrogen bond can be formed when a purine is present at position 35+ Yet, the type of interaction that occurs when a purine at position 35 is replaced by a pyrimidine has given rise to a long-standing debate (Quigley & Rich, 1976;von Ahsen et al+, 1997;Ashraf et al+, 1999a) in which the (U33)ribose + + + base(35) interaction was defined as "non ubiquitous" (Dix et al+, 1986) or "non-essential" (Ashraf et al+, 1999a)+ Here, by analyzing available tRNA crystal structures (Fig+ 1 and Table 1), relevant biochemical data, and results from molecular dynamics simulations , we pr...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation